Income effects and the inconvenience of private provision of public goods for bads : the case of recycling in Finland - Huhtala, Anni (Elsevier, 2010)
Absent or weak income effects reported in many contingent valuation studies have cast doubt on the reliability of the survey method. We find that the income effect depends on the type of public good in question: there is a negative income effect for willingness to pay for recycling, which requires time and effort for sorting, but a positive effect for the more convenient incineration. Hence, high-income (low-income) individuals may display less (more) effort on environmental behavior. This stresses the importance of comprehensive distributional analyses when assessing alternative environmental policies.
Keywords: Ma; Suomi; kierrätys; jätehuolto; kuluttajakäyttäytyminen; tulot; recycling; waste disposal; consumers; income; Finland; willingness to pay; preferences